Serum metalloproteinase-7 as a biomarker of progressive pulmonary fibrosis - Márcia Araújo; Marília Beltrão; Oksana Sokhatska; Natália Melo; Patrícia Caetano Mota; Helder Novais Bastos; André Terras; David Coelho; Luís Delgado; António Morais (ERJ Open Research)
Introduction Progressive pulmonary fibrosis (PPF) corresponds to any fibrotic interstitial lung disease (ILD) other than idiopathic pulmonary fibrosis (IPF) that presents clinical, physiological and/or radiological evidence of disease progression similar to IPF. Matrix metalloproteinases (MMPs) have been implicated in the pathogenesis of pulmonary fibrosis and are associated with disease progression and reduced survival in IPF and other fibrotic ILDs. This study aimed to investigate the role of serum levels of MMP-1 and MMP-7 in patients with fibrotic non-IPF ILD as possible biomarkers of patients at risk of developing PPF. Methods Newly diagnosed patients with fibrotic non-IPF ILD were included in this study. Serum levels of MMP-1 and MMP-7 were quantified at baseline and disease progression was monitored. PPF was defined according to the recent European Respiratory Society, American Thoracic Society, Japanese Respiratory Society and the Latin American Thoracic Society Clinical Practice Guidelines. Results 79 patients with fibrotic non-IPF ILDs were included and classified as having PPF or non-PPF. Significantly higher levels of MMP-7, but not MMP-1, were detected in the PPF group (p=0.01). MMP-7 was independently associated with PPF (adjusted OR 1.263, 95% CI 1.029–1.551; p=0.026) after adjustment for sex, age and smoking history. A cut-off value of 3.53 ng·mL−1 for serum MMP-7 levels had a sensitivity of 61% and a specificity of 74% for predicting PPF in non-IPF ILDs. Conclusions In patients with fibrotic non-IPF ILDs, serum MMP-7 levels were significantly greater in the subgroup of patients meeting the PPF criteria at follow-up. This can be considered and further investigated as a possible biomarker to identify fibrotic ILD patients at risk of PPF.